Social policies and sensibilities in the 21st century: an analysis from the population receiving cash transfers - Cena, Rebeca Beatriz (2023)
This article aims to address the sensibilities of the population receiving social policies in a specific context such as the Covid-19 Pandemic. In this framework, the results derived from interviews with young people receiving social policies are explored. It conclude inhabiting the youths intervened by social policies. The need to carry out inquiry processes that open, problematize, identify the folds through which social policies make society, in this case, youth, is identified